Usage Patterns of Electric Bicycles: An Analysis of the WeBike Project - Christian Gorenflo; Ivan Rios; Lukasz Golab; Srinivasan Keshav (Journal of Advanced Transportation)
This paper presents an analysis of data collected through the Waterloo WeBike project: a field trial in which over 30 sensor-equipped electric bicycles (e-bikes) were given to members of the University of Waterloo for personal use. Our dataset includes e-bike trips and battery charging sessions spanning nearly three years, from summer 2014 until spring 2017. We also conducted three surveys both before and during the trial. Our main findings were that the primary purpose of the e-bikes in our trial was for commuting, with most trips lasting less than 20 minutes and most trips taking place in the summer months. Our battery charging analysis revealed no evidence of range anxiety, and our analysis of survey results showed little correlation between anticipated and actual use. Furthermore, when asked about their opinions about various modes of transportation, our participants rated regular bicycles higher than e-bikes even after becoming familiar with e-bikes through the field trial. Based on our analysis, we draw several conclusions, including the fact that the general population in Canada is still unaware of e-bikes and their potential. Moreover, e-bike manufacturers should target sales to nonbike users, such as seniors, rather than trying to displace sales of regular bicycles.